Historias de vida de madres de hijos con discapacidad. Centro Centinelas de la vida. San Luis de Pambil. 2021 - Guadalupe Michelle, Pulgar Toapanta (2021)
Purpose: to know the life stories of mothers of children with disabilities at the Centinelas de la Vida Center. San Luis de Pambil, Bolivar-Ecuador 2021. Methodology: qualitative approach, type of case study with phenomenological and narrative design, whose data collection was carried out through a semi-structured in-depth interview, prior to the signing of the informed consent, eight mothers of children and adolescents of the institution analyzed were selected, who met the inclusion criteria. Results: the mothers felt confusion and sadness when they found out about the disability of their sons and daughters since they never imagined having children like this, it was hard for them to accept the disability, they have not been victims of rejection, the caregivers have presented stress, musculoskeletal pain and headaches due to the physical effort they make when moving their children. Among the main care they provide are rehabilitation therapies, personal hygiene, food and clothing. Regarding family support, most of them receive economic aid, care and moral support. Conclusions: the positive and pleasant feelings on the part of the caregivers are joy, strength and satisfaction when they see that their children are able to do some activity autonomously, despite the physical and mental exhaustion they continue to provide care. Limited training for their care and that of their children with disabilities. Family support is not sufficient for the care of their children, as they have considered at some point resuming their studies, work and personal relationships.